1989
DOI: 10.1111/j.1365-2222.1989.tb02363.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic components of Candida albicans identified by immunoblot analysis

Abstract: Allergenic components of Candida albicans fractionated by SDS-polyacrylamide gel electrophoresis (PAGE) and transferred to nitrocellulose membranes were identified using sera from 30 asthmatic patients who showed positive skin test and RAST (radio-allergosorbent test) to C. albicans. The IgE-binding yeast components in the complex antigen preparation were then detected by reaction with enzyme-labelled anti-human IgE antibodies. They were confirmed by Coomassie blue R-250 staining of the membrane to visualize a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
(11 reference statements)
0
22
1
Order By: Relevance
“…Using sera from 30 asthmatic patients with a positive skin test and IgE Abs to C. albicans, IgE immunoblotting of C. albicans extract showed that Cand a 1 had the highest frequency, being recognized by 23 (77%) patients. 164 Cand a 3 is 20-kD peroxisomal protein, which has 62% sequence identity with a hypothetical protein (YDR533c) from Saccharomyces cerevisiae. 165 Nine (56%) of 16 asthmatic sera with positive serum IgE Abs tests to C. albicans displayed positivity to Cand a 3 in IgE immunoblotting.…”
Section: Candidamentioning
confidence: 99%
“…Using sera from 30 asthmatic patients with a positive skin test and IgE Abs to C. albicans, IgE immunoblotting of C. albicans extract showed that Cand a 1 had the highest frequency, being recognized by 23 (77%) patients. 164 Cand a 3 is 20-kD peroxisomal protein, which has 62% sequence identity with a hypothetical protein (YDR533c) from Saccharomyces cerevisiae. 165 Nine (56%) of 16 asthmatic sera with positive serum IgE Abs tests to C. albicans displayed positivity to Cand a 3 in IgE immunoblotting.…”
Section: Candidamentioning
confidence: 99%
“…3, number 16) were identified as ADH1. ADH has also been reported as a candidal allergen present in sera from asthmatic or allergic patients [22,23], and as an antigen recognised by sera from patients with autoimmune polyglandular syndrome type I [24]. Table 2 gives a list of the antigens identified by microsequencing (spot numbers 1, 10, 15, 19 and 30).…”
Section: By Immunoblot Analysismentioning
confidence: 99%
“…binding profiles have varied among patients [11,12,[17][18][19][21][22][23]. Some workers have detected antibodies to immunodominant antigens which have a similar molecular mass to those which react with antibodies produced during disseminated candidosis [11,12,22].…”
mentioning
confidence: 99%